CTNI-48. NOVEL TREATMENT OF END STAGE RECURRENT GLIOBLASTOMA TREATED WITH A NONINVASIVE ONCOMAGNETIC DEVICE USING OSCILLATING MAGNETIC FIELDS – A NEW AND POWERFUL NONINVASIVE THERAPY - Helekar, Santosh (Neuro Oncol, 2020)
Noninvasive treatment with alternating electric fields at 200 kHz (Optune therapy) has been approved for recurrent and newly diagnosed glioblastoma (GBM). We have recently tested and confirmed in vitro, and in patient derived xenografted mouse models, the oncolytic potential of powerful newly developed device generating oscillating magnetic fields (OMF) using rotating magnets. This device is completely different and has different mechanisms of action than Optune therapy. We report the successful treatment of an endstage recurrent GBM in a 53-year-old man. The patient had undergone radical surgical excision and standard of care chemoradiotherapy, as well as experimental gene therapy for a left frontal tumor. 18 months after this treatment, there was recurrence with progressive enlargement and leptomeningeal spread, making the patient’s condition not suitable for further treatment. We conducted a 5-week treatment (followed by a pause of one week) consisting of daily exposure (on weekdays) with intermittent OMF. The patient tolerated the treatment well. At 4 weeks there was a progressive reduction of the contrast-enhanced tumor (CET) volume to less than 60% of the pre-treatment volume on magnetic resonance imaging scans. Caregiver report indicated mild subjective improvement in speech and cognitive function. The daily decrease in volume was correlated with the amount of daily treatment, with longer treatments showing an increase in shrinkage of the CET volume. After the treatment pause in the 6th week, there was an apparent increase in CET volume. However, a marked reduction in the choline peak and an increase in the lipid peak on a proton magnetic resonance spectrogram of the tumor at this timepoint documented that this represented necrotic tissue. We are excited about this new and powerful treatment for glioblastoma and will present the details of treatment and imaging studies during therapy.